2016
DOI: 10.1002/2016rs005957
|View full text |Cite
|
Sign up to set email alerts
|

F region ionosphere effects on the mapping accuracy of SuperDARN HF radar echoes

Abstract: Structured particle precipitation in the cusp is an important source for the generation of F region ionospheric irregularities. The equatorward boundaries of broad Doppler spectral width in Super Dual Auroral Radar Network (SuperDARN) data and the concurrent OI 630.0 nm auroral emission are good empirical proxies for the dayside open‐closed field line boundary. However, SuperDARN currently employs a simple virtual model to determine the location of its echoes, instead of a direct calculation of the radio wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
0
8
0
1
Order By: Relevance
“…In this study only channel A data are used. With a distance to the first range gate of 180 km and 75 sampled range gates at each beam (each range gate is 45 km long), range gates 40–45 typically correspond to the location of Ny‐Ålesund, depending on propagation conditions [e.g., Chen et al ., , ; Yeoman et al ., ]. This is due to the fact that SuperDARN currently employs a simple virtual model, i.e., assuming a fixed scattering height, to determine the location of its echoes, instead of a direct calculation of the ray path.…”
Section: Data and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study only channel A data are used. With a distance to the first range gate of 180 km and 75 sampled range gates at each beam (each range gate is 45 km long), range gates 40–45 typically correspond to the location of Ny‐Ålesund, depending on propagation conditions [e.g., Chen et al ., , ; Yeoman et al ., ]. This is due to the fact that SuperDARN currently employs a simple virtual model, i.e., assuming a fixed scattering height, to determine the location of its echoes, instead of a direct calculation of the ray path.…”
Section: Data and Instrumentationmentioning
confidence: 99%
“…This is due to the fact that SuperDARN currently employs a simple virtual model, i.e., assuming a fixed scattering height, to determine the location of its echoes, instead of a direct calculation of the ray path. A recent statistical observation [ Chen et al ., ] of the SuperDARN Finland radar spectral width boundary, transferring from narrow to broad, showed that the location of radar echoes near Svalbard is, on average, overestimated by ~2° (~1°) latitude in the poleward direction during solar maxima (solar minima). This is consistent with the theoretical analysis of Chisham et al .…”
Section: Data and Instrumentationmentioning
confidence: 99%
“…As HF radio waves propagate, the emergence of additional ionospheric layers leads to the emergence of additional propagation paths [Tsunoda et al, 2016], and, as a result, complicates matching of the radar range (group delay of a signal) and azimuth to real positions of scattering objects or directions to them [Reinisch et al, 1997;Chen et al, 2016;Warrington et al, 2016]. The frequency dependence of propagation paths causes strong phase distortions, thus making the detection of complex signals over long paths even more difficult.…”
Section: Over-the-horizon Radiolocation As a Methods For Monitoring Space Weather Effectsmentioning
confidence: 99%
“…При распространении КВ-радиоволн возникно-вение дополнительных ионосферных слоев приво-дит к возникновению дополнительных траекторий распространения и, как след-ствие, к усложнению привязки радиолокационной дальности (групповой задержки сигнала) и азимута к реальным положениям рассеивающих объектов или направлениям на них [Reinisch et al, 1997;Chen et al, 2016;Warrington et al, 2016]. Зависимость траекторий распростране-ния от частоты приводит к сильным фазовым иска-жениям сигнала, что дополнительно усложняет де-тектирование сложных сигналов на дальних трассах.…”
Section: загоризонтная радиолокация как метод контроля эффектов космиunclassified